Caring for the careers: A psychosocial support model for healthcare workers during a pandemic - Idah Moyo; Livhuwani Tshivhase; Azwihangwisi H. Mavhandu-Mudzusi (AOSIS, 2023)
Background: The coronavirus disease 2019 (COVID-19) pandemic has further placed additional stress on the already fragile and overstretched healthcare system in Zimbabwe. Most healthcare institutions reported staff shortages, inability to cope with the extra workload, burnout and the resultant psychological implications. Objectives: This study aimed to develop a psychosocial support model that sustains a support structure that will contribute to an enabling work environment promoting efficiency and effectiveness in response to public health emergencies. Method: Empirical findings from interpretive phenomenological analysis studies on healthcare workers' experiences during the COVID-19 in Zimbabwe formed the basis for model development. The model development in this study was informed by the work of Donabedian, Dickoff, James and Wiedenbach, Walker and Avant, Chinn, Kramer and Wilkes. Results: The developed model is described using the elements of Donabedian's framework (structure, process and outcome) and of Dickoff, James and Wiedenbach's (1968) practice theory elements (agents, recipients, context, process, dynamics and outcome) and within the national and international context of the COVID-19 pandemic. Conclusion: The fragile and under-resourced healthcare system has psychosocial implications to the well-being of healthcare workers. The utilisation of this model is critical and facilitates the provision of an enabling and supportive environment that facilitates efficiency in response activities during pandemics. Contribution: This study provides a reference guide in the provision of psychosocial support for healthcare workers particularly during public health emergencies. There is paucity of evidence focusing on the well-being of healthcare workers during a crisis, hence the significance of this study.